Nuclear heparanase-1 activity suppresses melanoma progression via its DNA-binding affinity - Yang, Y.; Bauer, Alexander; Komljenovic, Dorde; Schneider, Stefan W. (Oncogene, 2015)
Heparanase-1 (HPSE) plays a pivotal role in structural remodeling of the ECM and the glycocalyx, thus conferring protumorigenic, proangiogenic and prometastatic properties to many cancer entities. In addition to its extracellular function, recent studies suggest an intracellular activity of HPSE with a largely unknown significance during tumor progression. Therefore, we investigated the relevance of the dual functions of HPSE to malignant melanoma in vitro, as well as in different mouse melanoma models based on the intradermal or intravenous injection of melanoma cells. Consistent with its extracellular action, an HPSE deficiency led to a reduced shedding of the glycocalyx accompanied by a reduced availability of vascular endothelial growth factor, affecting tumor growth and vascularization. In contrast, we measured an elevated expression of the protumorigenic factors pentraxin-3, tissue factor, TNF-α and most prominently, MMP-9, upon HPSE knockdown. In vivo, an HPSE deficiency was related to increased lymph node metastasis. Since the inhibition of its extracellular function with heparin was unable to block the gene regulatory impact of HPSE, we proposed an intracellular mechanism. Immunostaining revealed a counter-staining of HPSE and NF-κB in the nucleus, suggesting a close relationship between both proteins. This finding was further supported by the discovery of a direct charge-driven molecular interaction between HPSE and DNA by using atomic force microscopy and a co-precipitation approach. Our findings are novel and point towards a dual function for HPSE in malignant melanoma with a protumorigenic extracellular activity and a tumor-suppressive nuclear action. The identification of molecular strategies to shuttle extracellular HPSE into the nuclei of cancer cells could provide new therapeutic options.
Gesehen am 10.12.2018